Papillary Thyroid Cancer—Aggressive Variants and Impact on Management: A Narrative Review (2020)
ABSTRACT: Introduction: Aggressive variants of papillary thyroid cancer (PTC) have been described with increasing frequency. These variants include diffuse sclerosing variant, tall cell variant, columnar cell variant, solid variant, and hobnail variant. Methods: We have performed a review of the more aggressive variants of PTC with respect to main characteristics, histological and molecular features, and the consequences that the knowledge of these variants should have in the treatment of the patients. Results: At the present time, we do not know the prognostic value of these aggressive PTC variants. The extent of the surgical treatment and adjuvant therapy necessary should be decided on the basis of the extent of the tumor at presentation and the opinion of experienced clinicians. Conclusion: These aggressive variants should be known by clinicians, to avoid underdiagnosis, and treated according to the latest recommendations in the literature. Keywords: Aggressive variants papillary thyroid cancer; Columnar cell variant; Diffuse sclerosis variant; Hobnail variant; Solid variant; Tall cell variant.